Peran Public Libraries dalam Model Literasi Politik Role of Public Libraries in Political Literacy Model - Albertoes Pramukti Narendra (PAX HUMANA, 2018)
AbstractThis paper discusses the role of public libraries in political literacy programs. This paper uses literature review methods from various sources. The data shows that there is still a knowledge gap in the political and citizenship fields in Indonesia. The impact of knowledge gaps in politics and citizenship makes it easy for people to be controlled by a variety of external factors which sometimes aim for negative things, and to reduce these gaps requires open learning so that people increasingly know their role as citizens. The Public Library has the duty to educate people's lives through various literacy programs or learning for the community. The Public Library is required to take part in political literacy programs so that citizens have knowledge and have an attitude in determining political choices. The results of the study show that there are several political literacy models that can be carried out by the Public Library in the context of political learning and citizenship for all levels of society. Recommendations that can be given include (1) Libraries need to be more pro-active in building networks with various parties so that they become a source of learning for people with various subjects. (2) The library develops literacy activities in various fields and carefully recognizes people who will use literacy programs. so that it can be useful.Keywords : Public Libraries, Political Literacy.